A study on the causes of design changes effecting the construction project performance - Nur Arfahanem, Mohamad Umpandi (2016)
Although many project time delays, cost overruns and quality defects particularly in the construction sector are attributed to design changes, the associated issues have not yet been thoroughly investigated. This relatively of this study is to study the causes of design changes effecting the performance of the construction project. Besides, it is to obtain the information about the causes of the design changes and then analyzed what are the causes of design changes that effect the performance of the construction project. The scopes of this research will cover the area in Peninsular Malaysia. It is focusing on the causes of design change in the engineering practitioners. The questionnaires were prepared and hand out to the person involved in construction project. Data gathering carried out by doing literature review, applying a questionnaire survey and making related interviews through contractor, owner and consultants company’s experts. According to the study thirty eight main of causes have been identified. These factors were then ranked on their relative importance, based on data from a questionnaire survey distributed to a wide range of professions in the industry. An analysis of the results found that the most influential factors contributing to design changes are design complexibility, non-compliances design with owner, and owner’s financial problem respectively.